Former à un métier par l’inter‑métiers en exploitant la vidéo : analyse de l’activité de cadres de l’éducation stagiaires lors d’une alloconfrontation collective inter‑métiers - Cyrille Gaudin; Sébastien Chaliès (Activités)
In France, an experimental device for the video-training of trainee education managers, based on interprofessional collective alloconfrontation, was developed, implemented and studied. In an interprofessional collective alloconfrontation, a group of professionals from different professions was confronted with a video recording of the professional activity of one of the group members. This design experiment was part of the French Institute of Education’s development of a video-training platform for education managers: Néopasscadres. As part of a research program on professional training the epistemological underpinnings of which derive from culturalist anthropology, the study was carried out with five volunteer trainee education managers, working in school management or inspection. To conduct the study, two categories of data were collected, transcribed verbatim, and analyzed: the video recording of the collective interprofessional alloconfrontation, and the participants’ self-confrontation interviews. The results provide a description and analysis of the activity of the trainee education managers involved in the interprofessional collective alloconfrontation. On this basis, we outlined the circumstances for video-based interprofessional training.